Diachronous Growth of the Altyn Tagh Mountains: Constraints on Propagation of the Northern Tibetan Margin From (U‐Th)/He Dating. Issue 7 (5th July 2018) - Shi, Wenbei; Wang, Fei; Yang, Liekun; Wu, Lin; Zhang, Weibin
Abstract: The sinistral Altyn Tagh strike‐slip fault demarcates the northern boundary of the Qinghai‐Tibetan Plateau; however, the significance and timing of activity along the fault are debated. Here new apatite and zircon (U‐Th)/He data are presented, revealing the exhumation history of the Altyn Tagh Mountains from crustal depths of ~2–7 km. Studies of rock samples from the Altun Shan region show that they were located close to the surface during the Early Cretaceous and remained so until about 40 Ma. Samples from the Subei and Dangjin Pass areas, on the other hand, record a period of rapid exhumation at 20 ± 2 Ma, and samples from the Qiemo area record a period of continuous exhumation between ~20 and 12 Ma at a rate of 0.046 − 0.013 + 0.007  mm/year, plus a further rapid cooling event at 7–5.5 Ma. Thus, significantly more exhumation has occurred toward the southwestern section of the Altyn Tagh Fault Zone, indicating a decrease in tectonic uplift toward the northeast since the Miocene. During the late Miocene, the Tarim Block began to subduct beneath the northern Tibetan margin, resulting in rapid exhumation of the central section of the Altyn Tagh Fault Zone. In accordance with previous studies, the present results support a model of northward propagation and expansion of the Qinghai‐Tibetan Plateau during the Cenozoic. Key Points: New apatite and zircon (U‐Th)/He age data from the Altyn Tagh Mountains reveal rapid exhumation in the Subei and Dangjin Pass areas at ~20 Ma Rapid exhumation of the central section of the Altyn Tagh Mountains occurred between 7 and 5.5 Ma The Qinghai‐Tibetan Plateau has propagated northward during the Cenozoic